Development and Quality Characteristics Studies of Tomato Paste Stored at Different Temperatures - Safdar, Muhammad Naeem; Mumtaz, Amer; Amjad, Muhammad; Siddiqui, Nouman; Hameed, Tabassum (Pakistan Journal of Nutrition, 2010)
A comparative study was done to determine the most suitable storage temperature for tomato paste at which there would be minimum damage to the product quality. Tomato paste samples were prepared, 0.1% sodium benzoate preservative added, stored at 25oC, 6oC and -10oC and were analyzed for chemical parameters as well as subjected to sensory evaluation at 30 days storage intervals till 240 days. A gradual increase in Total Soluble Solids (TSS) and acidity was observed during storage whereas pH and ascorbic acid were decreased. These changes were more pronounced at 25oC than at 6oC and -10oC. Results of sensory evaluation revealed that samples stored at lower temperatures such as 6oC and -10oC remained acceptable after 240 days storage. However, samples were rejected organoleptically at higher temperature storage i.e. 25oC.